2021
DOI: 10.3390/ijms22052522
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effects of Developmental Trauma on Neurotransmitter Systems Using Functional Molecular Imaging

Abstract: Early life stress (ELS) is strongly associated with psychiatric disorders such as anxiety, depression, and schizophrenia in adulthood. To date, biological, behavioral, and structural aspects of ELS have been studied extensively, but their functional effects remain unclear. Here, we examined NeuroPET studies of dopaminergic, glutamatergic, and serotonergic systems in ELS animal models. Maternal separation and restraint stress were used to generate single or complex developmental trauma. Body weights of animals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…In addition, since only restraint stress was used for a single trauma in the present study, the effect of other traumatic events is unknown. Our previous work has demonstrated that there is no significant difference between the two groups when evaluated in adulthood, after imposing single stressors such as MS or restraint stress during the developmental periods (17). However, sexual differences in MS were not explained because the study used only males.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…In addition, since only restraint stress was used for a single trauma in the present study, the effect of other traumatic events is unknown. Our previous work has demonstrated that there is no significant difference between the two groups when evaluated in adulthood, after imposing single stressors such as MS or restraint stress during the developmental periods (17). However, sexual differences in MS were not explained because the study used only males.…”
Section: Discussionmentioning
confidence: 91%
“…Rats were tested in an elevated plus-maze according to previously described procedures (17). The apparatus was made of acrylic and consisted of two closed arms with walls (40 cm × 10 cm × 30 cm) and two open arms (40 cm × 10 cm) connected by an open central platform (10 cm × 10 cm).…”
Section: Behavioral Tests Elevated Plus-mazementioning
confidence: 99%
See 2 more Smart Citations
“…We expected that early-life abuse would lead to attachment disorder in rat pups and to formation in later life of persistent neurobehavioral deficits not associated with the development of depression-like phenotype. It was shown that more pronounced disorders in behavior and neurotransmission were observed in rats subjected to complex aversive influences during brain development [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%